Socialização de futuros professores em situações de estágio curricular - Sambugari, Márcia Regina do Nascimento (2010)
The aim of the research was to investigate, during the development of curricular training, the occurrence of socialization between the teachers of Initial Grades of Fundamental Education in public schools and the students, during their training. The students come from a public university in the state of Mato Grosso do Sul, where they take the Pedagogy course. The study identified the interventions and the students practices and reactions during the situations experienced in the classroom internal relations, on the exercise of the teaching function. Based on Pierre Bourdieu s, Basil Bernstein s and Randall Collins s sociological perspective with conceptual categories, socialization was seen as an exchanging relation between the future teachers and the teachers, according to each one s incorporated dispositions, involving a set of classification and framing, which, depending on the interactions, may or may not favor an adequate environment for the transmission and the maintenance of the practices related to the performance of the teaching work. Considering the students previous school, social and family experiences, during which they developed their own views about the teaching work, the study proposed the research question: What are the teachers interferences on the students incorporation and confrontation related to the teaching work? The data were collected during observation sessions along the teaching training of four students and the teachers who had them in their classrooms. A questionnaire was also applied, so as to characterize the subjects. The meetings that take place at the university, in order to discuss the trainings, were recorded. The students wrote about their experience in diaries. Interviews were made with the subjects involved. The analyses showed that the students previous experiences have a meaningful force on their actions and reactions during the training, understood with the use of Pierre Bourdieu s habitus. The students manifested a matrix that generated behaviors, perceptions and thoughts, which changed (or not) certain teachers patterns. It was possible to see the presence of teachings, whether by means of the instructional discourse that demonstrates the knowledge power over different actions and notions conveyed in the classroom, and that favors the acquisition of competences, whether by means of a regulative discourse, exercising controls, giving orders, delimitating each one s relations and identities in the classroom. Whenever the framing was strong, the teachers exercised the social control over their pupils and the students in training. It was also possible to see that there were ritualistic chains of interaction, that is, each classroom, in their own way, had an action chain that composed rituals and repetitive everyday actions, both related to the interactions with the pupils and the interactions with the students. There was the establishment of alliances between the teachers and the students in training